Research progress on the pathogenesis and treatment of ventilator-induced diaphragm dysfunction - Jumei Zhang; Jianguo Feng; Jing Jia; Xiaobin Wang; Jun Zhou; Li Liu (Heliyon, 2023)
Prolonged controlled mechanical ventilation (CMV) can cause diaphragm fiber atrophy and inspiratory muscle weakness, resulting in diaphragmatic contractile dysfunction, called ventilator-induced diaphragm dysfunction (VIDD). VIDD is associated with higher rates of in-hospital deaths, nosocomial pneumonia, difficulty weaning from ventilators, and increased costs. Currently, appropriate clinical strategies to prevent and treat VIDD are unavailable, necessitating the importance of exploring the mechanisms of VIDD and suitable treatment options to reduce the healthcare burden. Numerous animal studies have demonstrated that ventilator-induced diaphragm dysfunction is associated with oxidative stress, increased protein hydrolysis, disuse atrophy, and calcium ion disorders. Therefore, this article summarizes the molecular pathogenesis and treatment of ventilator-induced diaphragm dysfunction in recent years so that it can be better served clinically and is essential to reduce the duration of mechanical ventilation use, intensive care unit (ICU) length of stay, and the medical burden.